Parvalbumin interneurons in the insular cortex control social familiarity and emotion recognition - Fujima, Shuhei; Sato, Masaaki; Nakai, Nobuhiro; Takumi, Toru (Cell reports (Cambridge), 2025)
The insular cortex is involved in various aspects of social behavior, yet the role and mechanism of its inhibitory regulation remain unclear. Through cell-type-specific microendoscopic calcium imaging and chemogenetic manipulation of neuronal activity, we discovered that parvalbumin-positive interneurons (PVINs) in the agranular insular cortex (aIC) are crucial in governing social familiarity and emotion recognition. Like pyramidal neurons (PNs), a specific subset of PVINs showed increased activity during peer interactions. Inhibiting PVINs led to a failure in losing the preference for familiar peers and hindered the rise in interactions with stressed individuals. These changes in behavior were linked to alterations in the proportion of PNs that showed activity corresponding with interactions with significant peers and the transitions in their social target specificity across sessions. Our findings highlight that PVINs provide context-dependent control over socioemotional behavior and the coding of social information by locally adjusting the social preference of individual PNs in the aIC. [Display omitted] •A subset of insular PV interneurons exhibits increased activity during social interactions.•Inhibiting PV interneurons prevents the loss of preference for familiar peers.•Inhibiting PV interneurons impairs the preference for stressed peers.•PV interneurons modulate pyramidal neuron activity related to social target preference. Fujima et al. employed microendoscopic calcium imaging and chemogenetic manipulation to elucidate the pivotal role of parvalbumin-positive interneurons in the agranular insular cortex. These neurons modulate social familiarity and emotion recognition by dynamically adjusting the responses of pyramidal neurons, thereby providing context-dependent control over socioemotional behavior.